(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2024)
Focuses on enriching speech and teaching logical thinking in the development of artistic thinking of children of preschool age. The role of morals and speech in the development of the behavioral motive of preschool children, as children understand their behavior, moral motives, i.e., the motivation to comply with social moral rules, become stronger, they are encouraged to act from the point of view of social interest, not egoistic interests of the child. It is explained on the basis of learning methods.